2015
DOI: 10.1111/avsc.12170
|View full text |Cite
|
Sign up to set email alerts
|

Responses of an ancient woodland field layer to soil translocation: methods and timing

Abstract: Questions: Do woodland field layer communities reassemble effectively after being translocated from a donor to a receptor site? Does the method of soil handling (turfing or loose-tipping) or the season of transfer determine the outcome?Location: A deciduous ancient coppice woodland in Kent, southeast England.Methods: Two methods of soil translocation were compared: loose-tipping, involving stripping a layer of topsoil and re-spreading it at a receptor site; and soil placement, in which soil turves were cut and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 44 publications
1
17
0
Order By: Relevance
“…The validity of the rationale is supported by other experiences in Australia that initial sowing/planting determines at least the first generation of the new woodland community and structure (Humphries, 2016). The experiences at Brickhouse Wood, Biggins Wood, Mold By-Pass, Stansted Airport have also shown that the commoner occurring ground layer species in the woodlands present in the first year of translocation generally survived to and beyond the development of a canopy in ten to twenty years later (Anderson, 2003;Craig et al, 2015;Buckley et al, 2017). However, longer-term monitoring has demonstrated that caution is needed, as the intended developing community may not happen, without intervention, owing to the dominance of some of the component species (Humphries, 2016).…”
Section: Monitoring and Its Evaluationmentioning
confidence: 82%
See 3 more Smart Citations
“…The validity of the rationale is supported by other experiences in Australia that initial sowing/planting determines at least the first generation of the new woodland community and structure (Humphries, 2016). The experiences at Brickhouse Wood, Biggins Wood, Mold By-Pass, Stansted Airport have also shown that the commoner occurring ground layer species in the woodlands present in the first year of translocation generally survived to and beyond the development of a canopy in ten to twenty years later (Anderson, 2003;Craig et al, 2015;Buckley et al, 2017). However, longer-term monitoring has demonstrated that caution is needed, as the intended developing community may not happen, without intervention, owing to the dominance of some of the component species (Humphries, 2016).…”
Section: Monitoring and Its Evaluationmentioning
confidence: 82%
“…For oak woodland of a similar structural condition as the Donor areas this is some 70 years into the future. From previous experiences reported for woodland translocations it is likely that it will be one or two decades before a functional canopy is likely to have developed (Anderson, 2003;Craig et al, 2015;Buckley et al, 2017). The data from these reports suggest that the initial vegetation, even after 1-3 years, can be indicative of the type and nature of the future woodland.…”
Section: Monitoring and Its Evaluationmentioning
confidence: 84%
See 2 more Smart Citations
“…This study clearly shows the wide diversity of the soils that have been deposited or have according to the different types of exploitation and rehabilitation been undertaken formerly. If the positive impact of the diversity of certain modes of quarrying have already been demonstrated with regard to the flora (Chenot et al, 2017;Craig et al, 2015;Prach et al, 2013;Vécrin and Muller, 2003), and the fauna (Adamopoulou and Legakis, 2006), few studies have focused on the impact on the diversity of the soils developed relative to the original situation (Jarvis and Walton, 2012). Thirty years after the rehabilitation process, the reconstituted Technosols present little significant difference with the reference steppe, whatever the physical or chemical parameter measured.…”
Section: Discussionmentioning
confidence: 99%